Fibroblast Growth Factor Signaling in Metabolic Regulation - Nies, Vera J. M.; Sancar, Gencer; Liu, Weilin; van Zutphen, Tim; Struik, Dicky; Yu, Ruth T.; Atkins, Annette R.; Evans, Ronald M.; Jonker, Johan W.; Downes, Michael Robert (Frontiers in Endocrinology, 2016)
The prevalence of obesity is a growing health problem. Obesity is strongly associated with several comorbidities, such as non-alcoholic fatty liver disease, certain cancers, insulin resistance and type 2 diabetes, which all reduce life expectancy and life quality. Several drugs have been put forward in order to treat these diseases, but many of them have detrimental side effects. The unexpected role of the family of fibroblast growth factors in the regulation of energy metabolism provides new approaches to the treatment of metabolic diseases, and offers a valuable tool to gain more insight into metabolic regulation. The known beneficial effects of FGF19 and FGF21 on metabolism, together with recently discovered similar effects of FGF1 suggest that FGFs and their derivatives carry great potential as novel therapeutics to treat metabolic conditions. To facilitate the development of new therapies with improved targeting and minimal side effects, a better understanding of the molecular mechanism of action of FGFs is needed. In this review we will discuss what is currently known about the physiological roles of FGF signaling in tissues important for metabolic homeostasis. In addition, we will discuss current concepts regarding their pharmacological properties and effector tissues in the context of metabolic disease. Also the recent progress in the development of FGF variants will be reviewed. Our goal is to provide a comprehensive overview of the current concepts and consensuses regarding FGF signaling in metabolic health and disease, and to provide starting points for the development of FGF-based therapies against metabolic conditions.